Using Dalbavancin for the Treatment of Acute Bacterial Skin and Skin Structure Infections (ABSSSIs) in Obese Patients: A Real-Life, Single-Center Observational Study - Alessandra Oliva; Flavia Petrucci; Cristiana Leanza; Marco Rivano Capparuccia; Michela Comi; Claudio Mastroianni (Antibiotics)
Background/Objectives: Obesity is an established risk factor for several infective conditions, including Acute Bacterial Skin and Skin Structure Infections (ABSSSIs), with a rising trend in their incidence expected in this population. Although numerous antibiotics are available for the prevention and treatment of ABSSSIs, their characterization in obese patients is not a regulatory mandate, highlighting a knowledge gap in this field. Dalbavancin (DAL) is the first approved long-acting antibiotic for the treatment of ABSSSIs. The aim of the study was to describe the clinical effectiveness of DAL in the treatment of ABSSSI, with or without concomitant osteoarticular infections (OAIs), in obese patients compared with non-obese patients. Furthermore, we compared the effectiveness of DAL and intravenous standard of care (SOC) regimens in a subgroup of obese patients with ABSSSI. Results: Overall, 45 subjects treated with DAL (12 obese and 33 non-obese) and 8 obese subjects treated with SOC regimens (1:1 ratio) were included. Obese patients treated with DAL had a similar clinical resolution to non-obese patients. However, obese patients tended to have a better cure rate in ABSSSI than OAI. The subgroup of obese patients with ABSSSI had a high clinical resolution, which was comparable to that of SOC. DAL was overall highly tolerated in obese patients. Methods: Over a three-year period, hospitalized subjects with ABSSSI who were treated with DAL were included. Patients were further divided into two groups according to the presence/absence of obesity (BMI ≥ 30 kg/m2). Furthermore, obese patients treated with DAL were compared with obese patients treated with SOC (1:1 ratio). Conclusions: In our real-world study, DAL confirmed its high effectiveness in the treatment of ABSSSI, including in a difficult-to-treat population such as obese patients.